DEVELOPMENT OF DIGITAL MODULE FOR ELECTRIC VEHICLE CONVERSION (Universitas Pendidikan Indonesia, 2024)
The Indonesian government strongly supports the conversion of fuel-based vehicle drive systems to electric motorbikes. The convenience obtained due to the conversion of this vehicle receives subsidies from the government in the form of incentives or discounted financial assistance. Few citizen in Indonesia not understand what spare parts are used, what specifications should be used. Based on this, the development of a digital electric vehicle conversion module is necessary, because during the current transition period for fuel oil vehicles to electricity, there are still no conversion books/modules available. This research uses research and development methods or design research and development (RD) which involves a 4D model (definition, design, development and dissemination). The participants in this research were 5 media expert validators and 4 media expert validators to validate the feasibility of developing a digital module for electric vehicle conversion. The research results showed that the digital module structure consists of the initial part, namely the digital module cover, digital module identity sheet, table of contents, and foreword. The content section is the cover of the sub-material, the cover of the sub-chapter of the material, and the description of the material. The final part is the bibliography and author biography. The contents of this digital electric vehicle conversion module include material related to electric vehicles, namely electric vehicles, history of electric vehicles, components (electric motor, controller, battery and onboard charger), electric vehicle conversion and safety. This digital module, seen from a media and meta perspective, is said to be